(untitled) (JOURNAL OF ADVANCES IN CHEMISTRY, 2016)
Â Â The complexes of azo dye 5-(4-aminoantipyrineazo)-8-hyroxyquinoline (L) with cupper (II) and zinc (II) Ions were synthesized. Characterization of these azo dyes complexes have been done on the basis of elemental analysis and IR techniques. The work involves a study of optimum conditions (time, pH, sequence of addition and temperature effects) for forming the complexes. The spectra of the complexes have been studied for a range of concentrations which Lambert â€“ Beer’s law were obeyed with sensitivity of the spectrophotometric method in terms of molar absorptivity 1.6Ã—104Â and 1.2Ã—104Â l .mol-1.cm-1 for zinc and cupper azo dyes complexes respectively .The stoichiometry of the complexes has been found to be 1:2 (metal : ligand). The overall stability constants were determined by the corresponding solutions method. The interferences effects of the foreign ions were studied. The biological activity of two complexes with two type of Bacteria (Clostridium botulinum and Escherichia Coli) were also studied.